Follicular fluid oxidative stress biomarkers and ART outcomes in PCOS women undergoing in vitro fertilization: A cross-sectional study - Kaivalya Gongadashetti; Pankush Gupta; Rima Dada; Neena Malhotra (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Polycystic ovarian syndrome (PCOS) is the most common cause of anovulatory infertility. Oxidative stress (OS), which plays an important role in determining the developmental competence of an oocyte, may be involved in understanding infertility and poor outcomes cycles in PCOS women undergoing in vitro fertilization (IVF). Objective: To measure OS biomarkers in the follicular fluid of PCOS women undergoing IVF. Materials and Methods: In this cross-sectional study, 100 women with PCOS (n = 43) and tubal factor (n = 57) undergoing IVF, who were referred to a tertiary medical center between January 2016 and September 2017 were enrolled. OS markers like reactive oxygen species (ROS), total antioxidant capacity (TAC), and 8-Isoprostane (8-IP) were tested in the follicular fluid and various IVF outcomes in the form of oocytes retrieved, fertilized, cleavage rate, grading of embryos and pregnancy outcomes were compared between the two groups. Results: The results indicated that the levels of ROS, TAC, and 8-IP were higher in the PCOS group compared to the tubal group (p = 0.21, p = 0.95, and p < 0.05, respectively). Biomarkers based on the number of retrieved oocytes, cleavage rate, and grades of embryos did not differ significantly in the two groups. The median ROS, TAC, and 8-IP were not significantly different in the two groups in relation to the pregnancies, although the 8-IP levels were significantly raised in the PCOS women who had a miscarriage (p = 0.02). Conclusion: This study concluded the possible role of OS in PCOS women with increased higher level of 8-IP biomarker as a potential biomarker that needs further evaluation.